ANALYSIS OF THE EFFECTIVENESS AND EFFICIENCY OF THE REGIONAL REVENUE AND EXPENDITURE BUDGET AT THE SALATIGA CITY REGIONAL REVENUE AND EXPENDITURE MANAGEMENT AGENCY (BPKPD) FOR THE YEARS 2021–2024 - Sidiq Herlambang Nugroho; Wikan Budi Utami; Suprihati Suprihati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study aims to analyze the effectiveness and efficiency of the Regional Revenue and Expenditure Budget (APBD) at the Regional Financial and Revenue Management Agency (BPKPD) of Salatiga City during the period 2021–2024. The research method used is descriptive with a quantitative approach. The data used are secondary data in the form of Budget Realization Reports (LRA) obtained from BPKPD of Salatiga City. Data collection was carried out using documentation methods, while data analysis techniques included variance analysis, regional financial independence ratio, effectiveness ratio of Regional Original Revenue (PAD), and expenditure efficiency ratio. The results of the study indicate that the revenue variance during the observation period is consistently positive, meaning that the realization of revenue exceeds the budgeted target. The regional financial independence ratio ranges from 43.93% to 52.54%, indicating a fairly independent category. The effectiveness ratio of PAD shows a very effective performance, as all values exceed 100%. Meanwhile, the expenditure variance shows negative values, indicating that actual expenditures are lower than the budget, resulting in budget savings. The expenditure efficiency ratio ranges from 89.06% to 93.64%, which indicates that the management of regional expenditures is efficient. In conclusion, the financial performance of the APBD management at BPKPD of Salatiga City during the period 2021–2024 can be categorized as good. However, improvements are still needed, particularly in enhancing regional financial independence to reduce reliance on central government transfers